A CRITICAL ASSESSMENT OF HEALTH TREATMENT SERVICES IN INDIA TO GUARANTEE THE EDUCATION OF ACCESSIBLE PROJECTS AND THE USAGE OF THOSE SERVICES. (International Journal of Food and Nutritional Sciences, 2022)
Healthcare access has become a social equity issue. It's vital to plan and distribute health resources depending on present healthcare accessibility. Healthcare capacity, population demand, and geographic impedance are three important factors to consider when assessing geographical accessibility. Healthcare accessibility refers to the ease with which services in health care can be obtained in a certain location. The National Rural Health Mission (NRHM) was established to improve the delivery of health treatment in rural areas. The health-care system in rural areas has vastly improved. The initiative had a significant impact on maternal and child health. This study employs the descriptive research approach. For the survey, a closed-ended questionnaire was used. A study was done to explain an agree/disagree opinion with 65 respondents agreeing, 57 respondents strongly agreeing, 43 respondents disagreeing, and 35 respondents strongly disagreeing among a population sample of 200 people. The study indicated that India's current healthcare inequities must be addressed by greatly expanding general health spending and implementing effective universal healthcare coverage. Patient satisfaction is determined by the services in health care provided, as well as the service providers' reliability and honesty.